EVALUASI PELAKSANAAN CLASSROOM ASSESSMENT PADA MATA PELAJARAN DI SD INPRES KECAMATAN PALLANGGA (Implementasi Evaluasi Program Model Formatif) - Cayati Cayati (Phinisi Integration Review, 2023)
The purpose of this research to evaluate the application of  classroom assessment  implementation  about: (1) the classroom assessment techniques, and (2) the classroom assessment procedures. This assessment was population survey research by using purposive sampling. The location of the research were in SDI Tallang-Tallang, SDI Tetebatu 1, and SDI Pangkabinanga. The evaluation model was formative from Michael Scriven. The data collected throug instruments, interviews, observations, and documentations. The data  analysis by using qualitative analysis technique. The result of the research indicate:  (1) the classroom assessment technique held by teacher, according to the principal and the students,  was still dominant on written, observation, practical, assignmet, and oral test, (2) the classroom assessment held by teacher with good catagories were written, observation, practical, assignment and oral test, while portfolio assessment technique, journal, self assessment, and among students assessment was not developed, (3) the teacher assessment procedure was not fulfill national education standard yet. The evaluation result about the aspect component, technique, and classroom assesment procedure of SDI teachers in Pallangga District is not carried out well yet, it was caused by the limited of science and lack of training given to the teachers.Tujuan penelitian ini adalah untuk mengevaluasi pelaksanaan classroom assessment tentang: (1) teknik-teknik classroom assessment, dan (2) prosedur classroom assessment. Penilaian ini adalah penelitian survei populasi. Teknik pengambilan sampel adalah purposive sample. Lokasi penelitian adalah SDI Tallang-Tallang, SDI Tetebatu 1, dan SDI Pangkabinanga. Model evaluasi adalah model formatif dari Michael Scriven. Pengumpulan data diperoleh melalui angket, wawancara, observasi, dan dokumentasi. Teknik analisa data yang digunakan adalah teknik analisis kualitatif. Hasil penelitian menunjukkan: (1) teknik classroom assessment  yang dilaksanakan guru, menurut kepala sekolah dasar inpres dan murid masih dominan pada tes tertulis, observasi, tes praktik,  penilaian tugas, dan tes lisan, (2) teknik classroom assessment  yang telah dilaksanakan guru dengan kategori baik adalah teknik tes tertulis, observasi, tes praktik, penilaian tugas dan tes lisan, sedangkan teknik penilaian portofolio, jurnal, penilaian diri, dan penilaian antarteman belum dikembangkan sebagaimana mestinya, (3) prosedur penilaian yang ditempuh guru belum sepenuhnya memenuhi sebagaimana yang terdapat dalam panduan penilaian mata pelajaran ilmu pengetahuan dan teknologi. Hasil evaluasi tentang komponen teknik dan prosedur penilaian kelas, guru SDI Kecamatan Pallanga belum terlaksana  dengan baik, hal ini akibat keterbatasan pengetahuan dan kurangnya pelatihan.